2017
DOI: 10.1080/0142159x.2017.1324137
|View full text |Cite
|
Sign up to set email alerts
|

Cartoon versus traditional self-study handouts for medical students: CARTOON randomized controlled trial

Abstract: Objective: The objective of this study is to compare the effectiveness of a "cartoon-style" handout with a "traditional-style" handout in a self-study assignment for preclinical medical students. Methods: Third-year medical students (n ¼ 93) at the Faculty of Medicine Ramathibodi Hospital, Mahidol University, took a pre-learning assessment of their knowledge of intercostal chest drainage. They were then randomly allocated to receive either a "cartoon-style" or a "traditional-style" handout on the same topic. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In accordance with the current results, it is believed that manga-based approaches may enable the combination of cognitive understanding based on narrative story-telling to provide practical knowledge in a general lifestyle context as well as the effects of visual image stimuli on sensory understanding and reduced psychological burden. Nevertheless, the overall small effect size observed in the results of the current study is consistent with those of previous randomized controlled trials (Junhasavasdikul et al, 2017 ; Kovacs et al, 2011 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with the current results, it is believed that manga-based approaches may enable the combination of cognitive understanding based on narrative story-telling to provide practical knowledge in a general lifestyle context as well as the effects of visual image stimuli on sensory understanding and reduced psychological burden. Nevertheless, the overall small effect size observed in the results of the current study is consistent with those of previous randomized controlled trials (Junhasavasdikul et al, 2017 ; Kovacs et al, 2011 ).…”
Section: Discussionsupporting
confidence: 93%
“…A previous systematic review revealed that the application of manga positively influenced health care settings (Branscum & Sharma, 2009 ). Several randomized controlled trials reported a small effect on initiatives of health behavior change for promoting general health (Junhasavasdikul et al, 2017 ) and for preventing back pain (Kovacs et al, 2011 ). However, other studies challenged the application of health promotion manga or comics for a range of patient education or health education initiatives, such as programs for promoting physical activity and healthy diet (Baranowski et al, 2002 ; Branscum, Sharma, Wang, Wilson, & Rojas-Guyler, 2013a , 2013b ; Leung et al, 2017 ; Leung, Tripicchio, Agaronov, & Hou, 2014 ; Manes, Liu, Burke, & Dworkin, 2014 ); the prevention infectious diseases (Bieri, Yuan et al, 2013 ; Yuan, Manderson, Tempongko, Wei, & Aiguo, 2000 ), HIV/AIDS (Dworkin et al, 2013 ; Gillmore et al, 1997 ), and cancer (Lyzun & McMullen, 2009 ; Risi et al, 2004 ); immunization (Diamond et al, 2016 ; Muzumdar & Nania, 2015 ; Muzumdar & Pantaleo, 2017 ); smoking cessation (Bush et al, 2005 ); reduction of disease-related stigma (el-Setouhy & Rio, 2003 ), education on pesticide exposure and health (Liebman, Juárez, Leyva, & Corona, 2007 ); prevention of accidents among children (Cardenas & Simons-Morton, 1993 ); and patient education (Maxwell, Simmons, Franklin, Arnold, & Pall, 2014 ; Shigehatake et al, 2014 ).…”
mentioning
confidence: 99%
“…Graphic novel methods have been used to teach concepts in medicine [28], business [30], history [31], literacy [32], and secondary school [33]. Studies in these domains have demonstrated that graphic novels and illustrated content resulted in greater recall [30], enhanced test performance and reading behavior [34], greater reading motivation [2], and comparable decision-making while requiring less reading time [35] than text-only formats. Overall, graphic novel formats have resulted in greater memory of content, greater ease of processing, and greater motivation to engage with content, than text alone.…”
Section: Why a Graphic Novel Approach?mentioning
confidence: 99%
“…Previous studies have shown that comics improve student [2], patient [3], and resident [4] understanding of medical information and often outperform traditional instructional methods. Junhasavasdikul et al [2] found better third-year student results on a thoracostomy quiz in students randomized to a comic compared with a text-based handout. Brand et al [3] showed that patients having angiography given a comic explaining the procedure had better understanding and satisfaction and less anxiety than patients receiving only standard informed consent.We performed a randomized trial to compare knowledge level by exposure to a comic or a traditional journal article describing P values among firstyear medical students.…”
mentioning
confidence: 99%
“…Fig. 1) [5] modeled on the Calvin and Hobbes [6] comic strip with elements from Peanuts [7], The Flintstones [8], The Jetsons [9], Batman [10], and other classic comics tropes [11,12] or (2) an article from a statistics journal [13]. Participants completed an online in-class eight-question (four true-or-false, three multiple choice, one sentence completion) prereading quiz (e-only Appendix 1) and on the same day received their reading assignment.…”
mentioning
confidence: 99%